2016
DOI: 10.1016/j.scitotenv.2016.03.157
|View full text |Cite
|
Sign up to set email alerts
|

Significant cooling effect on the surface due to soot particles over Brahmaputra River Valley region, India: An impact on regional climate

Abstract: Black carbon (BC) is an important atmospheric aerosol constituent that affects the climate by absorbing (directly) the sunlight and modifying cloud characteristics (indirectly). Here, we present first time yearlong measurements of BC and carbon monoxide (CO) from an urban location of Guwahati located in the Brahmaputra River valley (BRV) in the northeast region of India from 1st July 2013 to 30th June 2014. Daily BC concentrations varied within the range of 2.86 to 11.56μgm(-3) with an annual average of 7.17±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 104 publications
2
9
1
Order By: Relevance
“…In this paper, we compared the BC mass concentration of JSR and RNC with other cities of India. The mean BC mass concentration reported at JSR (15.87 μgm −3 ; Present study) was found to be higher as compared to Agra 29 9.5 μgm −3 , Ahmedabad 30 8.3 μgm −3 ; Dhanbad 11 6.5 μgm −3 ;, Guwahati 31 7.2 μgm −3 , Hyderabad 32 9.7 μgm −3 , Visakhapatam 33 4.8 μgm −3 , Kolkata 34 5.0 μgm −3 , Ranchi 35 8.5 μgm −3 ; New Delhi 36 17.4 μgm −3 , Patana 37 9.1 μgm −3 , Pune 38 13.8 μgm −3 , Srinagar 39 6.0 μgm −3 , Tirupati 40 1.0 μgm −3 , Varanasi 35 μgm −3 ;Present study). And BC concentration reported at present study sites (JSR and RNC) was found to be low as compared to Kharagpur 33 21.0 μgm −3 , National Capital Territory 41 33.9 μgm −3 and Raipur 42 23.0 μgm −3 .…”
Section: Comparison Of Bc Mass Concentration At a Different Locationcontrasting
confidence: 43%
“…In this paper, we compared the BC mass concentration of JSR and RNC with other cities of India. The mean BC mass concentration reported at JSR (15.87 μgm −3 ; Present study) was found to be higher as compared to Agra 29 9.5 μgm −3 , Ahmedabad 30 8.3 μgm −3 ; Dhanbad 11 6.5 μgm −3 ;, Guwahati 31 7.2 μgm −3 , Hyderabad 32 9.7 μgm −3 , Visakhapatam 33 4.8 μgm −3 , Kolkata 34 5.0 μgm −3 , Ranchi 35 8.5 μgm −3 ; New Delhi 36 17.4 μgm −3 , Patana 37 9.1 μgm −3 , Pune 38 13.8 μgm −3 , Srinagar 39 6.0 μgm −3 , Tirupati 40 1.0 μgm −3 , Varanasi 35 μgm −3 ;Present study). And BC concentration reported at present study sites (JSR and RNC) was found to be low as compared to Kharagpur 33 21.0 μgm −3 , National Capital Territory 41 33.9 μgm −3 and Raipur 42 23.0 μgm −3 .…”
Section: Comparison Of Bc Mass Concentration At a Different Locationcontrasting
confidence: 43%
“…Atmospheric aerosols play a crucial role in affecting global climate by absorbing sunlight and modifying cloud characteristics. , Nevertheless, an evident gap between ground-based observations and numerical modeling still remains. For instance, the oxidation of volatile organic compounds (VOCs) is one of the major contributors to the amount of secondary organic aerosols (SOAs) in the atmosphere, but great prediction uncertainties for the two constituents are inevitable due to unknown atmospheric processes, e.g. a different aging process where VOCs are transformed to SOA in the presence of oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum BC-ARF in the atmosphere was found during the winter season in a study over Dhanbad (28.0 W m -2 ) during 2013 , over Hyderabad (33.5 Wm -2 ) during 2009-2010 (Dumka et al, 2013), and over New Delhi (65.8 W m -2 ) during 2010 (Surendran et al, 2013). Bhat et al, (2017) for Guwahati during 2014 (Tiwari et al, 2016b) and Dhanbad during 2013 , respectively . The BC-ARF in the atmosphere over Hyderabad during 2009-2010 were reported to be 33.5 ± 7.0 W m -2 in winter, 31.8 ± 12.9 W m -2 in pre-monsoon, 18.9 ± 6.7 W m -2 in postmonsoon, and 13.2± 1.7 W m -2 in monsoon seasons (Dumka et al, 2013), which is less as compared to the values reported over Varanasi in the present study.…”
Section: Resultsmentioning
confidence: 90%
“…However, the resultant BC radiative forcing in the atmosphere (ARF ATM) is found in the range of +9. over Guwahati during 2014 with the highest BC-ARF in the atmosphere during the pre-monsoon season, followed by the winter season than post-monsoon and monsoon season (Tiwari et al, 2016b). Maximum BC-ARF in the atmosphere was found during the winter season in a study over Dhanbad (28.0 W m -2 ) during 2013 , over Hyderabad (33.5 Wm -2 ) during 2009-2010 (Dumka et al, 2013), and over New Delhi (65.8 W m -2 ) during 2010 (Surendran et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation